2016
DOI: 10.1016/j.ijbiomac.2015.09.062
|View full text |Cite
|
Sign up to set email alerts
|

Yeast expressed ArtinM shares structure, carbohydrate recognition, and biological effects with native ArtinM

Abstract: Recent advances in glycobiology have revealed the essential role of lectins in deciphering the glycocodes at the cell surface to generate important biological signaling responses. ArtinM, a d-mannose-binding lectin isolated from the seeds of jackfruit (Artocarpus heterophyllus), is composed of 16 kDa subunits that are associated to form a homotetramer. Native ArtinM (n-ArtinM) exerts immunomodulatory and regenerative effects, but the potential pharmaceutical applicability of the lectin is highly limited by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Although ArtinM recognizes primarily Manα1-3(Manα1-6)Man, which is the common core of N-glycans, the fine specificity of its binding is further determined by a secondary subsite of recognition. It interacts with other carbohydrate residues (Fuc and GlucNAc), which may be contained in the N-glycan, resulting in the particular binding property exhibited by this lectin 32 , 33 , 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ArtinM recognizes primarily Manα1-3(Manα1-6)Man, which is the common core of N-glycans, the fine specificity of its binding is further determined by a secondary subsite of recognition. It interacts with other carbohydrate residues (Fuc and GlucNAc), which may be contained in the N-glycan, resulting in the particular binding property exhibited by this lectin 32 , 33 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…This activity was attributed to ArtinM interaction with TLR2 N-glycans 31 , which is followed by IL-12 production and establishment of Th1 immunity. The ArtinM effects were shown to depend on carbohydrate recognition because direct binding to TLR2 was inhibited by the trimannoside specifically targeted by ArtinM 32 , 33 , which constitutes the core of N-glycans. These data demonstrated that a carbohydrate recognition protein might function as a TLR agonist and exert immunomodulatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…This research confirmed the preference of the ArtinM primary site for probes having the core structure Manα1–3[Manα1–6]Manβ1–4. It also showed the contribution of the secondary site of ArtinM to enhancing the affinity of the CRD for probes containing Fucα1–6 or GlcNAcα1–2 associated with Manα1–3[Manα1–6]Manβ1–4 [ 47 , 48 , 49 ]. The core structure Manα1–3[Manα1–6]Manβ1–4 recognized by ArtinM is also targeted by Morniga M [ 50 , 51 ], which is consistent with the marked correlation between the glycan-binding specificities and phylogenies of ArtinM and Morniga M [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…n-ArtinM was obtained from a saline extract of Artocarpus heterophyllus (jackfruit) seeds [6] . Saccharomyces cerevisiae BJ3501 was used to express y-ArtinM and the lectin was obtained by yeast lysis [1] . n-ArtinM and y-ArtinM were purified by affinity chromatography on a D -mannose column coupled to AKTA Purifier (GE Healthcare, Bio-Science Inc. Germany), previously equilibrated with phosphate-buffered saline (PBS) containing 0.5 M NaCl.…”
Section: Materials and Methods And Datamentioning
confidence: 99%
“… This article contains data related to the researc.h article entitled “Yeast-derived ArtinM shares structure, carbohydrate recognition, and biological effects with native ArtinM” by Cecílio et al (2015) [1] . ArtinM, a D -mannose-binding lectin isolated from the seeds of Artocarpus heterophyllus, exerts immunomodulatory and regenerative activities through its Carbohydrate Recognition Domain (CRD) (Souza et al, 2013; Mariano et al, 2014 [2] , [3] ).…”
mentioning
confidence: 99%